Taxonomic analysis reveals host preference of rare fungi in endophytes of Vitis vinifera from the Czech Republic - Kolařík, Miroslav; Vrublevskaya, Maria; Kajzrová, Soňa; Kulišová, Markéta; Kolouchová, Irena Jarošová (Folia microbiologica, 2023)
This paper represents the results of screening a diversity of fungal endophytes associated with Vitis vinifera leaves and canes in the Czech Republic. The characterization of strains is based on morphological and phylogenetic analyses of ITS, EF1α and TUB2 sequence data. Our strain selection covers 16 species and seven orders belonging to Ascomycota and Basidiomycota. Together with ubiquitous fungi, we report on several poorly known plant-associated fungi, Angustimassarina quercicola (= A. coryli, a synonym proposed in this study) and Pleurophoma pleurospora. Other species, such as Didymella negriana, D. variabilis, Neosetophoma sp. (species identical or sister to N. rosae), Phragmocamarosporium qujingensis and Sporocadus rosigena, have so far been little known and rarely found, but are frequent on V. vinifera in different parts of the world and obviously belong to a microbiota with a strong preference for this plant. Detailed taxonomical identification allowed us to identify species with apparent stable associations with V. vinifera, for which further interactions with V. vinifera can be expected. Our study is the first to focus on V. vinifera endophytes in Central Europe and expands the knowledge about their taxonomy, ecology and geography.
Keywords: Basidiomycota; Česká republika; Phylogeny; endofyty; Fungi; Czech Republic; Phragmocamarosporium qujingensis; Neosetophoma; Sporocadus; Vitis vinifera; houby; Angustimassarina; Ecology; Vitis; Didymella; fylogeneze; Endophytes; Host preference